Long-Term Impact of Oral Contraceptive Use in Adult Life on Postmenopausal Hypertension - Dahiya , Simran; Mehta, Tejal; Malik, Abhinav; Bhuma, Ritish; Dhalani, Mayank; Agarwal, Srishty; Trivedi, Yash Vardhan; Jain, Rohit (Eastern Journal of Medical Sciences, 2025)
Oral contraceptive pills (OCP) are widely utilized globally for both contraceptive and non-contraceptive purposes, with combined oral contraceptive pills being the more commonly prescribed type compared to progestin-only pills. Despite their efficacy, OCPs are associated with various adverse effects, including the development of hypertension. Hypertension, a prevalent condition among older women, particularly those over 60 years of age, has been linked to prior OCP use, potentially contributing to an elevated risk of cardiovascular and cerebrovascular disorders. The mechanisms underlying OCP-induced hypertension include activation of the renin-angiotensin-aldosterone system (RAAS), endothelial dysfunction, vascular remodeling, inflammation, and oxidative stress. Evidence suggests that estrogen-containing OCPs can exert long-term effects on blood pressure regulation, increasing the likelihood of hypertension, particularly with prolonged use or higher estrogen doses. However, newer formulations with lower estrogen doses have been shown to mitigate this risk. Additionally, certain progestins, such as drospirenone, may exert protective effects by reducing blood pressure. Ongoing research and vigilant monitoring are essential to further elucidate these associations and optimize OCP formulations for safer use.